Seismic response and damage analysis of buildings supported on flexible soils. - Rodriguez, Mario E. (Earthquake engineering & structural dynamics.)
The investigation reported in this paper studies the effects of soil structure interaction (SSI) on the seismic response and damage of building-foundation systems. A simple structural model is used for conducting a parametric study using a typical record obtained in the soft soil area of Mexico City during the 1985 earthquake. Peak response parameters chosen for this study were the roof displacement relative to the base and the hysteretic energy dissipated by the simple structural model. A damage parameter is also evaluated for investigating the SSI effects on the seismic damage of buildings. The results indicate that in most cases of inelastic response, SSI effects can be evaluated considering the rigid base case and the SSI period.